2018
DOI: 10.1007/s10086-017-1691-7
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of touching hinoki cypress (Chamaecyparis obtusa)

Abstract: This study aimed to clarify the physiological effects of touching hinoki cypress (hereinafter called "hinoki") (Chamaecyparis obtusa) wood with the palm of the right hand on brain activity and autonomic nervous activity. Twenty-two female university students (mean age 21.1 ± 0.2 years) participated in the study. As an indicator of brain activity, oxyhemoglobin (oxy-Hb) concentrations were measured in the left/right prefrontal cortex using near-infrared time-resolved spectroscopy. Heart rate variability (HRV) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 42 publications
1
39
1
Order By: Relevance
“…Considering that we want to continue the previous studies [11][12][13][14]16], a total of 27 female Japanese university students (mean age: 21.9 ± 1.9 years) were included in the current study. None of the participants reported any physiological or psychiatric disorders in their personal histories, and all were non-smokers.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that we want to continue the previous studies [11][12][13][14]16], a total of 27 female Japanese university students (mean age: 21.9 ± 1.9 years) were included in the current study. None of the participants reported any physiological or psychiatric disorders in their personal histories, and all were non-smokers.…”
Section: Participantsmentioning
confidence: 99%
“…Conversely, very few reports regarding tactile stimuli were investigated. In response to this, recent research has begun to focus on the effects of tactile stimulation from wood by using the prefrontal cortex and autonomic nerve activity as indexes [11][12][13][14]. The physiological effects of palm contact with wood have been investigated for sugi (Japanese cedar, Cryptomeria japonica) [11], hinoki (Japanese cypress, Chamaecyparis obtusa) [12], and white oak (Quercus alba) [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, significant decreases in the oxy-Hb concentration were noted in the left and right prefrontal cortices. In the previous TRS studies using various sensory stimuli, significant differences were noted in only the left prefrontal cortex [34,37,50], only the right prefrontal cortex [33,35,39,40,51,52], or both cortices [36,38,[53][54][55]. Thus, it is not clear whether a significant decrease in the oxy-Hb concentration occurs in the right prefrontal cortex, left prefrontal cortex, or both cortices, and further investigations are needed in the future.…”
Section: Discussionmentioning
confidence: 93%
“…This finding suggests that NIRS enables the detection of brain activity in the prefrontal cortex region. Some previous studies reported that the oxy-Hb concentration in the prefrontal cortex significantly reduced and the subjective relaxed feeling significantly improved simultaneously in participants who had been exposed to visual [33][34][35], tactile [36][37][38], auditory [39], or olfactory [40] stimulation.…”
Section: Vertical Imagementioning
confidence: 98%